Diagnostic Accuracy of Bronchoalveolar Lavage in Diagnosis of Ple-ural Tuberculosis among Suspected Cases of Pleural TB - Raniyah Akhter, Aneel Kumar, Neelam Khatri, Nausheen Saifullah, Nadeem Ahmed Rizvi (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the accuracy of bronchoalveolar lavage in diagnosis of pleural tuberculosis among suspected cases of pleural tuberculosis using biopsy. Study design: Descriptive, cross-sectional. Place and duration of study: Department of Chest Medicine, JPMC, Karachi from 1st August 2017 to 31st January 2018. Methodology: One hundred and thirty six patients with cases of pleural tuberculosis of age 18-55 years and both genders were included. Patients with anti-tuberculosis drugs, pneumonia, tonsillitis, pharyngitis, obstructive pulmonary disease and platelet function disorders, thrombocytopenia or coagulation factors disorder were excluded. 30-50 ml of bronchoalveolar fluid was carried out through fiberoptic bronchoscopy. Three milliliters of 4% lignocaine was used as pre-medication and 3 ml of 2% lignocaine was used during bronchoscopy. Results: In BAL positive patients, 73 (true positive) had pleural tuberculosis and 9 (false positive) had no pleural tuberculosis on biopsy. Among 54, BAL negative patients, 5 (false negative) had pleural tuberculosis on biopsy whereas 49 (true negative) had no pleural tuberculosis on biopsy. Overall sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of BAL in diagnosis of pleural tuberculosis among suspected cases of pleural tuberculosis using biopsy as gold standard was 93.59%, 84.48%, 89.02%, 90.74% and 89.71% respectively. Conclusion: The diagnostic accuracy of bronchoalveolar lavage in diagnosis of pleural tuberculosis among suspected cases of pleural tuberculosis is quite high.